A patchwork past [large type] - Gould, Leslie, 1962- (Gould, Leslie, 1962-. Plain patterns, 2021)
"Few are pleased Sophie Deiner has returned to her Amish community, but a sudden illness leaves her no choice. She befriends a group of migrant workers but is appalled by their living conditions. She soon finds her advocacy for change opposed by her ex, the farm foreman, and that her efforts only makes things worse. Has she chosen a fight she can't win?"--